Composite RAID for rapid prototyping data grid. (4th February 2011) - Uehara, Minoru
Recently, the demand of low-cost large-scale storages increases. We developed Virtual Large-Scale Disks (VLSDs) toolkit for constructing virtual disk-based distributed storages, which aggregate free spaces of individual disks. However, to construct such large-scale data grid, we need to understand how to implement more complex RAID. In this paper, we propose Composite RAID (CRAID) that is a design methodology for rapid prototyping complex RAID. CRAID can represent more complex RAID than the conventional methodology. In this paper, we introduce two examples of CRAID-based complex RAIDs and then we show how effective CRAID is.